Increased cardiovascular risk and reduced quality of life are highly prevalent among individuals with hepatitis C. Issue 1 (26th August 2020) - McPherson, Stuart; Gosrani, Shion; Hogg, Sarah; Patel, Preya; Wetten, Aaron; Welton, Rachael; Hallsworth, Kate; Campbell, Matthew
Abstract : Objective: Hepatitis C virus (HCV) infection is common. Although treatment is effective, with oral antivirals curing >95% of patients, most individuals have comorbidities that persist long term. Therefore, our aim was to determine the prevalence of potentially modifiable health problems in patients with HCV and develop an HCV care bundle to identify and target comorbidities. Design: Cross-sectional, observational single-centre study that recruited consecutive patients with HCV from our viral hepatitis clinics. Data were collected on cardiovascular (CV) risk factors, lifestyle behaviours, anthropometry and health-related quality of life (HRQoL). QRISK 3 was used to predict 10-year CV event risk. Results: 100 patients were recruited (67% male, 93% white, median age 52 years (range 24–80); 71% were treated for HCV; 34% had cirrhosis; 14% had diabetes; 61% had hypertension; 31% had metabolic syndrome; and 54% were smokers). The median 10-year CV event risk was 8.3% (range 0.3%–63%). 45% had a predicted 10-year CV event risk of >10%. Only 10% of individuals were treated with statins and 27% with antihypertensives. 92% had a predicted 'heart age' greater than their chronological age (median difference +7 (−4 to +26) years). HRQoL was reduced in all SF36v2 domains in the cohort. Factors independently associated with HRQoL included cirrhosis, metabolic syndrome, history of mental health disorder, sedentary behaviour and HCV viraemia. Conclusion: A large proportion of patients with HCV presented with increased risk of CV events, and rates of smoking and sedentary behaviour were high, while prescribing of primary prophylaxis was infrequent. HRQoL was also reduced in the cohort. A 'care bundle' was developed to provide a structured approach to treating potentially modifiable health problems.